Emotions, Argumentation and Argumentativity: Insights from an Analysis of Newspapers Headlines in the Context of the Greek Crisis - Herman, Thierry; Serafis, Dimitris (Informal Logic)

(untitled) (Informal Logic, 2019)
The present paper examines how discursive representations and emotive constructions underpin an argumentative dynamic that emerges from apparently non-argumentative statements, like those found in newspaper headlines. Our data comes from Greek broadsheet newspapers in the polarized context of the Greek crisis. First, we outline an analytic synergy that scrutinizes representational meaning and the semiotization of emotions in headlines. We then move towards the reconstruction of the inferential passage, contained in the headlines, that unites the implicit standpoint with its supporting argument.